Pyrogenically produced zirconium-containing oxide coated mixed lithium transition metal oxide

A dry mixing process coats lithium transition metal oxides with heat-generated zirconium dioxide to address rapid aging in lithium batteries, enhancing cycle stability and performance by ensuring a uniform and strong adhesion of the coating.

JP7623359B2Active Publication Date: 2025-01-28EVONIK OPERATIONS GMBH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2022513406
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-27
Filing Date
2020-08-26
Publication Date
2025-01-28
Estimated Expiration
2040-08-26

AI Technical Summary

Technical Problem

Existing lithium batteries, particularly those with high nickel content, face rapid aging and performance degradation due to electrochemical deterioration mechanisms, leading to unstable crystal structures, electrolyte decomposition, and increased resistance, which reduces capacity and cycle life.

Method used

A mixed lithium transition metal oxide is coated with heat-generated zirconium dioxide or zirconium-containing oxides using a dry mixing process to improve adhesion and distribution, avoiding the use of solvents and ensuring a uniform coating.

Benefits of technology

The method enhances the cycle stability and performance of lithium batteries by providing a strong and uniform zirconium dioxide coating on the cathode material, improving capacity and extending the battery's life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007623359000001
    Figure 0007623359000001
  • Figure 0007623359000002
    Figure 0007623359000002
  • Figure 0007623359000003
    Figure 0007623359000003
Patent Text Reader

Abstract

A method for producing a coated mixed lithium transition metal oxide, comprising subjecting a mixed lithium transition metal oxide and pyrogenously produced zirconium dioxide and / or a pyrogenously produced mixed oxide containing zirconium to dry mixing using an electric mixing unit having a specific power of 0.05 to 1.5 kW per kg of mixed lithium transition metal oxide; the coated mixed lithium transition metal oxide obtainable by this method; a cathode for a lithium battery; and a lithium battery comprising such coated particles.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a coated mixed lithium transition metal oxide, to a coated mixed lithium transition metal oxide obtainable by this method, to a cathode for a lithium battery, and to a lithium battery comprising such a coated metal oxide.

[0002] In recent years, various energy storage technologies have attracted a great deal of public attention and have been the subject of intensive research and development in industry and academia. As energy storage technologies expand into devices such as mobile phones, camcorders, and laptops, and even electric vehicles, there is an increasing demand for high-energy density batteries to be used as power sources for such devices. Secondary lithium batteries are one of the most important battery types in use today.

[0003] Secondary lithium batteries usually consist of an anode made of a carbon material or a lithium metal alloy, a cathode made of lithium metal oxide, and an electrolyte in which a lithium salt is dissolved in an organic solvent. The separator in a lithium battery provides for the passage of lithium ions between the positive and negative electrodes during the charging and discharging processes.

[0004] One of the common problems with cathode materials is their rapid aging and therefore the loss of performance during cycling. This phenomenon is particularly relevant for nickel manganese cobalt mixed oxides (NMCs) with a high nickel content. The deactivation of the cathode materials occurs through several electrochemical degradation mechanisms. Ni in a highly delithiated state 4+ The crystal structure becomes unstable due to surface transformations such as the formation of NiO-like phases due to reduction and oxygen loss of NMC, and the rearrangement of transition metals. This phase transformation is associated with initial cracks appearing on the cathode particle surface and subsequent particle collapse. In addition, the electrolyte decomposes at the reactive surface of the NMC, and the electrolyte decomposition products are deposited at the interface of the cathode material, thereby increasing the resistance. In addition, the conductive salt LiPF commonly used in liquid electrolytes6 is the trace amount of H present in all commercial formulations. 2 It reacts with O to form HF. This highly reactive compound induces lattice distortion in the cathode material by dissolving transition metal ions from the surface of the cathode material into the electrolyte. All these degradation mechanisms result in reduced capacity, performance, and cycle life.

[0005] It is known that coating mixed lithium transition metal oxide particles with some metal oxides can suppress undesirable reactions with the electrolyte and electrode materials, thus improving the long-life stability of lithium batteries.

[0006] WO 00 / 70694 discloses mixed transition metal oxide particles coated with oxides or mixed oxides of Zr, Al, Zn, Y, Ce, Sn, Ca, Si, Sr, Mg, and Ti by suspending the uncoated particles in an organic solvent, mixing the suspension with a solution of hydrolyzable metal compounds and a hydrolysis solution, and then filtering off, drying, and calcining the coated particles.

[0007] US 2015 / 0340689 discloses a cathode active material (CAM) for lithium batteries comprising a transition metal oxide core and a coating layer comprising zirconium dioxide. Such coated CAMs are typically prepared by mixing a transition metal precursor with zirconium(IV) oxynitrate having an average particle size of less than 1 μm and calcining the so obtained mixture at 700° C. to form ZrO 2 The materials are prepared by forming a CAM coated with ZrO. An alternative embodiment (Example 5) shows that the transition metal precursor is mixed with zirconium(IV) dioxide having an average particle size of less than 1 μm, sourced from Aldrich Co, and the resulting coated CAM is calcined at 700° C. Analysis of these materials by SEM microscopy reveals that ZrO is present in the coating. 2 The average particle size of the particles is shown to be about 400 nm (FIG. 2, Analysis Example 1).

[0008] US 2016 / 0204414 describes a CAM for batteries with a non-aqueous electrolyte that includes a transition metal oxide core with a zirconium compound present on the surface of the core. The examples show the use of zirconium dioxide with an average particle size of 1 μm for coating the CAM.

[0009] CN 105161710 discloses a CAM comprising a transition metal mixed oxide core and a coating layer containing alumina or zirconia with a particle size of 5-100 nm. Thus, in Example 4, a CAM of formula LiNi 0.5 Co 0.2 Mn 0.3 Mg 0.02 O 2 The precursor of ZrO with a particle size of 20 nm 2 The CAM was mixed with SiO2 by ball milling, and the resulting coated CAM was calcined at 580 °C.

[0010] JP 2013-235666 A describes a ZrO alloy having a transition metal oxide core and a monoclinic crystal structure. 2 A CAM is described that includes a layer containing particles. 50 = LiNi with an average grain size of 10 μm 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 The particle is D 50 = ZrO with an average grain size of 27 nm 2 The particles are mixed at a rotation speed of 4000 rpm and then fired at 800°C.

[0011] The last two papers describe nanostructured ZrO with an average grain size of 20-30 nm. 2 Although particles are mentioned, no further details are given, such as the method of preparation or source of such particles. The average particle size given is ZrO 2Such small primary particles usually aggregate and agglomerate to form much larger particles in the μm range.

[0012] Journal of the Chinese Institute of Engineers, Vol. 28, No. 7, pp 1139-1151 (2005) 2 The powders were prepared by spray pyrolysis using the sol-gel method or mechanothermal method, with an average particle size of 500-600 nm. 2 In the latter method, LiCoO 2 The powder was ZrO in ethanol. 2 The dispersion is sonicated for 30 min, followed by slow evaporation of the solvent at 50° C. and calcination at 450° C. for 10 h.

[0013] Also, several mixed metal oxides containing zirconium have been reported for use in lithium batteries.

[0014] US Patent Publication No. 2017179544 discloses the preparation of lithium cathode materials doped with zirconium-based mixed metal oxides. Thus, in Example 1, Li 7 La 3 Zr 2 Al 0.07 O 12.0105 mixed metal salts and sintered the mixture at 1200 °C for 10 h, followed by the formation of mixed lithium transition metal oxides Li(Li 10 / 75 Ni 18 / 75 Co 9 / 75 Mn 38 / 75 )O 2 and then heated at 900 °C for 20 hours to form the lithium cathode material. 7 La 3 Zr 2 Al 0.07 O 12.0105It is clear that only large sized sintered particles of 0.1 to 0.5 mm were usable.

[0015] The cathode materials of lithium batteries have been modified with Al to improve their cycling performance. 2 O 3 , TiO 2 , and ZrO 2 However, practical methods for improving battery longevity are often limited. Thus, in the case of zirconium dioxide, commercially available nano-sized ZrO 2 The use of particles often results in uneven distribution and large agglomerates of ZrO on the surface of the core cathode material. 2 Particles result (see FIG. 2 for such an example) and as a result, minimal or no improvement in cycling performance is observed when compared to uncoated cathode materials.

[0016] The problem addressed by the present invention is to provide modified mixed lithium transition metal oxides as cathode materials, particularly of the high nickel NMC type, for use in lithium batteries, which should provide higher cycling stability than that of unmodified materials.

[0017] In the course of careful experimentation, it was surprisingly found that pyrogenously produced zirconium dioxide, or pyrogenously produced mixed oxides containing zirconium, can be successfully used for coating mixed lithium transition metal oxides applicable as cathodes for lithium batteries.

[0018] The present invention provides a method for producing a coated mixed lithium transition metal oxide, which comprises subjecting a mixed lithium transition metal oxide and pyrogenously produced zirconium dioxide and / or a pyrogenously produced mixed oxide comprising zirconium to dry mixing using an electric mixing unit having a specific power of 0.05-1.5 kW / kg of mixed lithium transition metal oxide.

[0019] The term "electrical mixing unit" in the context of the present invention relates to any mixing device which operates by the supply of electrical energy.

[0020] Power is the rate per unit time at which electrical energy is transferred by an electrical circuit. The term "specific power" in the context of the present invention relates to the power per kg of mixed lithium transition metal oxide delivered by the electrical mixing unit during the mixing process.

[0021] Dry mixing is understood to mean that no liquid is added or used during the mixing process, i.e., for example, substantially dry powders are mixed together. However, it is possible that there are traces of moisture or some liquid other than water in the mixed raw materials, or that these contain water of crystallization. Preferably, the mixture of mixed lithium transition metal oxide and pyrogenically produced zirconium dioxide and / or pyrogenically produced mixed oxide containing zirconium contains less than 5% by weight, more preferably less than 3% by weight, more preferably less than 1% by weight of water and / or other liquids.

[0022] The dry mixing process of the present invention has several advantages over mixing processes involving wet coating, for example coating with a metal oxide-containing dispersion. Such wet coating processes entail the use of a solvent that needs to be evaporated after the completion of the coating process. The dry coating process of the present invention is therefore simpler and more economical than the wet coating processes known from the prior art. On the other hand, it has surprisingly been found that the dry coating process of the present invention also provides a better distribution of the metal oxide particles, including zirconium, on the surface of the mixed lithium transition metal oxide.

[0023] If a specific power used is less than 0.05 kW per kg of mixed lithium transition metal oxide, this will result in a non-uniform distribution of the zirconium dioxide, or mixed oxide containing zirconium, which may not be tightly bound to the lithium transition metal oxide core material.

[0024] A specific power above 1.5 kW per kg of mixed lithium transition metal oxide leads to weaker electrochemical properties, and there is a risk that the coating will become brittle and prone to cracking.

[0025] The nominal power of the mixing unit can vary in a wide range, for example, from 0.1 kW to 1000 kW. It is therefore possible to use laboratory-scale mixing units with a nominal power of 0.1 to 5 kW, or production-scale mixing units with a nominal power of 10 to 1000 kW. The nominal power is the nameplate and maximum absolute power of the mixing unit.

[0026] Similarly, the volume of the mixing unit can be varied over a wide range, e.g., from 0.1 L to 2.5 m 3 Thus, laboratory-scale mixing units with volumes from 0.1 to 10 L, or 0.1 to 2.5 m 3 It is possible to use production scale mixing units having capacities of

[0027] The term "volume of the mixing unit" in the context of the present invention refers to the maximum volume of the chamber of the electric mixing unit in which the substances to be mixed can be placed.

[0028] Preferably, in the method according to the invention, a compulsory mixer is used in the form of an intensive mixer with a high-speed mixing tool. It has been found that a speed of the mixing tool between 5 and 30 m / s, more preferably between 10 and 25 m / s, gives the best results. The term "mixing tool" in the context of the present invention refers to any object in the mixing unit that is capable of moving, for example rotating, shaking, etc., and thus mixing the contents of the mixing unit. Examples of such mixing tools are stirrers of various forms. Commercially available mixing units well suited for the method according to the invention are, for example, Henschel mixers or Eirich mixers.

[0029] The mixing time is preferably 0.1 to 120 minutes, more preferably 0.2 to 60 minutes, and most preferably 0.5 to 10 minutes.

[0030] Following the mixing, the mixture can be subjected to a heat treatment. Such a treatment can improve the bonding of the coating to the mixed lithium transition metal oxide particles. However, in the method according to the invention, this treatment is not necessary, since the zirconium dioxide or mixed oxide containing zirconium produced in this method is sufficiently strongly attached to the mixed lithium transition metal oxide. Therefore, a preferred embodiment of the method according to the invention does not include a heat treatment after mixing.

[0031] The best results for the deposition of zirconium oxide on mixed lithium transition metal oxides were obtained for zirconium dioxide and mixed oxides containing zirconium at 5 m 2 / g~200m 2 / g, more preferably 10m 2 / g~150m 2 / g, most preferably 15 to 100m 2 It has been found that this is obtained when the zeolite has a BET surface area of ​​100 / g. The BET surface area can be determined by nitrogen adsorption according to the Brunauer-Emmett-Teller procedure in accordance with DIN 9277:2014.

[0032] The zirconium dioxide and zirconium-containing mixed oxides used in the process according to the invention are prepared exothermically, ie by a pyrogenic process also known as the "fumed" process.

[0033] Such "pyrophoric" or "fumed" methods involve the reaction of the corresponding metal precursors in flame hydrolysis or flame oxidation in an oxyhydrogen flame to form metal oxides. This reaction initially forms highly dispersed, approximately spherical primary metal oxide particles, which in the further course of the reaction coalesce to form aggregates. These aggregates can then accumulate into agglomerates. In contrast to agglomerates, which can generally be relatively easily separated into aggregates by the introduction of energy, the aggregates are only further broken down by the intensive introduction of energy, if at all. The metal oxide powders can be partially broken down by suitable grinding and converted into particles in the nanometer (nm) range, which are advantageous for the present invention.

[0034] The preparation of pyrogenic zirconium dioxide is further described in EP 717008 A1 and WO 2009053232 A1.

[0035] The preparation of some pyrogenic mixed oxides containing zirconium is further described in WO2015173114.

[0036] Zirconium dioxide powders produced pyrogenically, in particular by flame hydrolysis, and other mixed metal oxides containing zirconium can be produced starting from zirconium halides, preferably zirconium chloride, as Zr precursors. 4and other metal precursors, if applicable, can be evaporated, and the resulting vapors, alone or together with a carrier gas, e.g. nitrogen, are mixed with other gases, i.e. air, oxygen, nitrogen, and hydrogen, in a mixing unit of a burner. These gases react with each other in a flame in a closed combustion chamber to produce zirconium dioxide (or mixed zirconium oxide) and waste gas. The hot waste gas and metal oxides are then cooled in a heat exchanger unit, the waste gas is separated from the metal oxide, and the halide residues adhering to the resulting metal oxide are removed by thermal treatment with moist air.

[0037] A flame spray pyrolysis (FSP) process suitable for preparing zirconium dioxide, or mixed metal oxides containing zirconium, may comprise the following steps: 1) atomizing a solution containing a zirconium precursor, for example with air or an inert gas, preferably using a multi-substance nozzle; 2) mixing a combustion gas, preferably hydrogen and / or methane, with air; and 3) burning the mixture in a flame into a reaction chamber surrounded by a casing; 4) Cooling the hot gases and solid products and then removing the solid products from the gases.

[0038] The preferred Zr metal precursors used to produce zirconium dioxide and mixed oxides containing zirconium by flame spray pyrolysis are zirconium carboxylates, particularly zirconium carboxylates of aliphatic carboxylic acids having 6 to 9 carbon atoms, such as zirconium 2-ethylhexanoate.

[0039] The other metal precursors required to produce the zirconium mixed metal oxide can be either inorganic compounds such as nitrates, chlorides, or organic compounds such as carboxylates.

[0040] The metal oxide precursors used can be dissolved in water or an organic solvent and then atomized. Suitable organic solvents include methanol, ethanol, n-propanol, isopropanol, n-butanol, tert-butanol, 2-propanone, 2-butanone, diethyl ether, tert-butyl methyl ether, tetrahydrofuran, C1-C8 carboxylic acids, ethyl acetate, toluene, petroleum, and mixtures thereof.

[0041] The pyrogenically produced zirconium dioxide and pyrogenically produced mixed oxides containing zirconium used in the process according to the invention are therefore in the form of aggregated primary particles, the numerical mean diameter of which is Transparent type Electron microscope law( Preferably, the numerical average diameter is 5-100 nm, more preferably 10-90 nm, and even more preferably 20-80 nm, as determined by TEM. This numerical average diameter can be determined by calculating the average size of at least 500 particles analyzed by TEM.

[0042] The average diameter of the aggregates of pyrogenically produced zirconium dioxide and pyrogenically produced mixed oxides containing zirconium is usually about 10-1000 nm, the average diameter of the aggregates is usually 1-2 μm. These average values ​​can be determined by the static light scattering (SLS) method in a suitable dispersion, for example in an aqueous dispersion. The aggregates and partially the aggregates can be broken, for example, by grinding or ultrasonicating the particles, whereby particles with a smaller particle size are obtained.

[0043] Preferably, the zirconium dioxide and / or mixed oxides containing zirconium have an average particle size d 50 is 10-150 nm, more preferably 20-130 nm, and even more preferably 30-120 nm, as determined by static light scattering (SLS) after 60 seconds of ultrasonic treatment at 25°C of a mixture consisting of 5% by weight of the particles and 95% by weight of a 0.5 g / L aqueous sodium pyrophosphate solution.

[0044] Thus, the pyrogenically produced zirconium dioxide and pyrogenically produced mixed oxides containing zirconium used in the process of the present invention are preferably characterized by high dispersibility, i.e., the ability to form relatively small particles, under mild ultrasonic treatment. It is believed that dispersion under such mild conditions correlates with the conditions during the dry coating process. This means that the aggregates of zirconium oxide are broken down in the mixing process of the present invention in a manner similar to ultrasonic treatment, allowing the formation of a uniform coating of transition metal oxide.

[0045] The span (d 90 -d 10 ) / d 50 is preferably 0.4 to 1.2, more preferably 0.5 to 1.1, and even more preferably 0.6 to 1.0, as determined by static light scattering (SLS) after 60 seconds of ultrasonic treatment at 25°C of a mixture consisting of 5% by weight of particles and 95% by weight of a 0.5 g / L aqueous sodium pyrophosphate solution.

[0046] Thus, the pyrogenically produced zirconium dioxide and pyrogenically produced mixed oxides containing zirconium used in the process of the present invention are preferably characterized by a relatively narrow particle size distribution, which helps to achieve a high quality zirconium oxide coating on the surface of the transition metal oxide.

[0047] d value 10 , d 50 , and d 90 is typically used to characterize the cumulative particle size distribution of a given sample. For example, d 10 The diameter is the diameter at which 10% of the sample volume is d 10 is the diameter of the particles less than d 50 is the volume of the sample that is 50% of the 50 The diameter of the particles is less than d 50 is also called the "volume median diameter" because it divides the sample evenly by volume, and d 90is the volume of the sample that is 90% d 90 The diameter of the particles is less than 1 mm.

[0048] Zirconium dioxide and mixed oxides containing zirconium are preferably hydrophilic in nature, i.e. they are not further treated with hydrophobic agents such as silanes after their synthesis by the pyrogenic process. The particles thus produced usually have a purity of at least 96% by weight, preferably at least 98% by weight, more preferably at least 99% by weight. The metal oxides containing zirconium may contain hafnium compounds in the form of hafnium dioxide. The proportion of hafnium dioxide is ZrO 2 The zirconium dioxide and mixed oxides containing zirconium used in the method of the present invention preferably contain the elements Cd, Ce, Fe, Na, Nb, P, Ti, Zn in proportions of less than 10 ppm and the elements Ba, Bi, Cr, K, Mn, Sb in proportions of less than 5 ppm, the sum of the proportions of all these elements being less than 100 ppm. The chloride content is preferably less than 0.5% by weight, more preferably 0.01 to 0.3% by weight, based on the mass of the metal oxide powder. The carbon proportion is preferably less than 0.2% by weight, more preferably 0.005% to 0.2% by weight, even more preferably 0.01% to 0.1% by weight, based on the mass of the metal oxide powder.

[0049] The mixed oxides containing zirconium may further contain lithium and, optionally, at least one of lanthanum and / or aluminum. The following mixed metal oxides containing zirconium are particularly preferred: LiZrO 3 and the general formula Li x La 3 Zr 2 M y O 8.5+0.5x+z Mixed oxides of Wherein, 6.5≦x≦8, preferably 7.0≦x≦7.5; 0≦y≦0.5, preferably 0≦x≦0.2; For M=Hf, Ga, Ge, Nb, Si, Sn, Sr, Ta, and Ti, z=2y; For M=Al, Sc, V, and Y, z=1.5y; For M=Ba, Ca, Mg, and Zn, z=y; Most preferably Li 7 La 3 Zr 2 O 12 .

[0050] The term "transition metal" in the context of the present invention includes the following elements: Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Nb, Mo, Ru, Rh, Pd, Ag, Cd, Ta, W, Re, Os, Ir, Pt, Au. Preferably, the transition metal is selected from the group consisting of nickel, manganese, cobalt, and mixtures thereof.

[0051] The mixed lithium transition metal oxides preferably used in the process according to the invention are selected from the group consisting of lithium-cobalt oxide, lithium-manganese oxide, lithium-nickel-cobalt oxide, lithium-nickel-manganese-cobalt oxide, lithium-nickel-cobalt-aluminum oxide, lithium-nickel-manganese oxide, or mixtures thereof.

[0052] The mixed lithium transition metal oxide is preferably of the general formula LiMO 2 wherein M is at least one transition metal selected from nickel, cobalt, manganese, more preferably M=Co or Ni x Mn y Co z where 0.3≦x≦0.9, 0≦y≦0.45, and 0≦z≦0.4.

[0053] General formula LiMO 2 The mixed lithium transition metal oxides may be further doped with at least one other metal oxide, particularly aluminum oxide and / or zirconium oxide.

[0054] The coated mixed lithium transition metal oxide preferably has a numerical average particle size of 2 to 20 μm, which can be determined by laser diffraction particle size analysis in accordance with ISO 13320:2009.

[0055] The proportion of zirconium dioxide and / or mixed oxides containing zirconium is preferably 0.05% by weight to 5% by weight, more preferably 0.1% by weight to 2% by weight, based on the total weight of the mixture of mixed lithium transition metal oxide and zirconium dioxide and / or mixed oxides containing zirconium used.

[0056] If the proportion of zirconium dioxide and / or mixed oxides containing zirconium is less than 0.05% by weight, the beneficial effect of the coating is usually still not observable, if it is more than 5% by weight, the beneficial effect of an additional amount of zirconium coating of more than 5% by weight is usually not observed.

[0057] The coated mixed lithium transition metal oxide preferably has a coating layer thickness of 10 to 200 nm, as determined by TEM analysis.

[0058] The present invention further provides a number average particle size d of 10 nm to 150 nm, preferably 20 nm to 130 nm, more preferably 30 nm to 120 nm. 50 The present invention provides a coated mixed lithium transition metal oxide comprising pyrogenously produced zirconium dioxide and / or pyrogenously produced mixed oxide containing zirconium on a surface of the mixed lithium transition metal oxide, the number average particle size d of the pyrogenously produced zirconium dioxide and / or pyrogenously produced mixed oxide containing zirconium in the coated mixed lithium transition metal oxide. 50 teeth, Transparent type The average particle size d for pyrogenically produced zirconium dioxide and / or pyrogenically produced mixed oxides containing zirconium used in the process of the present invention can be determined by analysis in electron microscopy (TEM). 50This average particle size d corresponds to 50 The value can be determined by static light scattering (SLS) after 60 seconds of ultrasonic treatment at 25° C. of a mixture consisting of 5% by weight of particles and 95% by weight of a 0.5 g / L aqueous solution of sodium pyrophosphate.

[0059] The coated mixed lithium transition metal oxide of the present invention is preferably obtainable by the method according to the present invention.

[0060] The further preferred features of the coated mixed lithium transition metal oxide, pyrogenously produced zirconium dioxide and / or pyrogenously produced mixed oxide comprising zirconium described above in preferred embodiments of the process according to the invention are also preferred features of the coated mixed lithium transition metal oxide, pyrogenously produced zirconium dioxide and / or pyrogenously produced mixed oxide comprising zirconium, respectively, with respect to the coated mixed lithium transition metal oxide according to the invention, irrespective of whether this is produced by the process of the invention or not.

[0061] The present invention further provides an active positive electrode material for a lithium battery comprising a coated mixed lithium transition metal oxide according to the present invention or a coated mixed lithium transition metal oxide obtainable by a method according to the present invention.

[0062] The positive electrode, or cathode, of a lithium battery typically includes a current collector and a layer of active cathode material formed on the current collector.

[0063] The current collector can be aluminum foil, copper foil, nickel foil, stainless steel foil, titanium foil, a polymer substrate coated with a conductive metal, or a combination thereof.

[0064] The active positive electrode material may include materials capable of reversibly inserting / desorbing lithium ions and are well known in the art. Such active cathode materials may include transition metal oxides, such as mixed oxides including Ni, Co, Mn, V or other transition metals and optionally lithium. Mixed lithium transition metal oxides (NMC) including nickel, manganese, and cobalt are particularly preferred.

[0065] The present invention also provides a lithium battery comprising a coated mixed lithium transition metal oxide or a coated mixed lithium transition metal oxide obtainable by the method according to the present invention.

[0066] A lithium battery of the invention may comprise, apart from the cathode, an anode, optionally a separator, and an electrolyte comprising a lithium salt or lithium compound.

[0067] The anode of the lithium battery may comprise any suitable material commonly used in secondary lithium batteries that is capable of reversibly inserting / desorbing lithium ions. Typical examples are carbonaceous materials, including crystalline carbon such as natural or artificial graphite in the form of plate-like, flake, spherical or fibrous types of graphite, soft carbon, hard carbon, mesophase pitch carbide, amorphous carbon such as calcined coke, or mixtures thereof. In addition, lithium metal or conversion materials (e.g., Si or Sn) can be used as the anode active material.

[0068] The electrolyte in a lithium battery can be in the form of a liquid, gel, or solid.

[0069] The liquid electrolyte of the lithium battery may include any suitable organic solvent commonly used in lithium batteries, such as anhydrous ethylene carbonate (EC), dimethyl carbonate (DMC), propylene carbonate, methyl ethyl carbonate, diethyl carbonate, gamma butyrolactone, dimethoxyethane, fluoroethylene carbonate, vinyl ethylene carbonate, or mixtures thereof.

[0070] The gel electrolyte includes a gelling polymer.

[0071] The solid electrolyte of a lithium battery may include an oxide, such as a lithium metal oxide, a sulfide, a phosphate, or a solid polymer.

[0072] The electrolyte of a lithium battery may contain a lithium salt. Examples of such lithium salts include lithium hexafluorophosphate (LiPF 6 ), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium perchlorate (LiClO 4 ), lithium tetrafluoroborate (LiBF 4 ), Li 2 SiF 6 , lithium triflate, LiN(SO 2 CF 2 CF 3 ) 2 and mixtures thereof.

[0073] The invention further provides the use of a coated mixed lithium transition metal oxide according to claim 12 or 13 in an active positive electrode material of a lithium battery. [Brief description of the drawings]

[0074] [Figure 1] FIG. 2 shows particle size distribution of fumed ZrO2. [Diagram 2] FIG. 1 shows the particle size distribution of “nano ZrO2”. [Diagram 3] FIG. 13 shows SEM-EDX mapping of Zr (white) on NMC coated with ZrO2 prepared by using fumed ZrO2. [Figure 4] FIG. 1 shows the results of analysis of NMC coated with “nano-ZrO2”. [Diagram 5] FIG. 13 is a diagram showing the results of a constant current cycle test.

[0075] Working Example Starting materials 40~60m 2 Fumed ZrO with a specific surface area (BET) of 100 / g 2 was prepared by flame spray pyrolysis according to Example 1 of WO2009053232.

[0076] 35m 2 The commercially available "nano-ZrO 2 ” Powder (particle size 20–30 nm) was sourced from ChemPUR Feinchemikalien und Forschungsbedarf GmbH.

[0077] 0.30~0.60m 2 / g BET surface area, median particle size d 50 Commercially available mixed lithium nickel manganese cobalt oxide powder NMC(7-1.5-1.5) (type PLB-H7) with a mean diameter of 10.6 ± 2 μm (measured by static laser scattering method) was procured from Linyi Gelon LIB Co.

[0078] Various ZrO 2 Type of particle size distribution Fumed ZrO 2 Or commercially available "Nano ZrO 2 " A sample of the powder (5 wt%) was dispersed in a solution of sodium pyrophosphate (0.5 g / L) in distilled water and treated in an external ultrasonic bath for 1 min at 25°C (160 W).

[0079] Figure 1 shows the fumed ZrO 2 Figure 1 shows the particle size distribution of nano-ZrO2 analyzed by static laser diffraction (SLS) using a laser diffraction particle size analyzer (HORIBA LA-950). 2 The particle size distribution of fumed ZrO 2 For the 100-kDa, a very narrow monomodal particle size distribution was detected (d 10 = 0.06014 μm, d 50 = 0.07751 μm, d 90 = 0.11406 μm, span = (d90 -d 10 ) / d 50 =0.7), ChemPUR's "Nano ZrO 2 For ", a broad bimodal distribution was detected, indicating large non-dispersed particles (d 10 = 0.10769 μm, d 50 = 3.16297 μm, d 90 = 5.80804 μm, span = (d 90 -d 10 ) / d 50 =1.8).

[0080] Example 1 First, NMC powder (217.8 g) was mixed with 2.2 g (1.0 wt%) of fumed ZrO in a high intensity laboratory mixer (Somakon mixer MP-GL with 0.5 L mixing unit) at 500 rpm (specific power: 350 W / kg NMC) for 1 min. 2 The mixing intensity was then increased to 2000 rpm (specific power: 800 W / kg NMC, tip speed of the mixing tool in the mixing unit: 10 m / s) and mixing was continued for 5 min to obtain the ZrO 2 Dry coating of NMC particles was achieved by

[0081] The coated NMC particles were coated with ZrO particles with thicknesses ranging from 10 to 200 nm, as determined by TEM analysis. 2 The coating layer is shown.

[0082] Comparative Example 1 The procedure of Example 1 was repeated exactly, with the only difference being that fumed ZrO 2 Instead of "nano ZrO 2 " The powder was used.

[0083] ZrO 2 SEM-EDX analysis of mixed lithium transition metal oxides coated with ZnO Figure 3 shows the fumed ZrO 2 ZrO was prepared by using 2Figure 4 shows the SEM-EDX mapping of Zr (white) on NMC coated with "nano-ZrO" (example 1). 2 3 and 4 show the results of an analysis of NMC coated with "ZrO2" (Comparative Example 1). The axes in Figures 3 and 4 indicate: x-axis = particle size; left y-axis = volume (%); right y-axis = cumulative volume (%). 2 The NMC mixed oxides dry coated with ZrO 2 The figure shows complete and uniform coverage of all NMC particles with relatively large ZrO 2 No agglomerates were detected, which is likely due to the nanostructured fumed ZrO 2 In addition, there is free unbound ZrO next to the NMC particles. 2 No particles were observed, indicating strong adhesion between the coating and the substrate (NMC). In contrast, Figure 5 shows that the "Nano ZrO 2 " Fine ZrO 2 This shows that only the particles are bonded to the surface of the NMC particles. 2 The particles are not dispersed, are not bonded, and are located next to the NMC particles, and as a result, the NMC particles are not completely covered with zirconium oxide.

[0084] 1. Preparation of Electrodes Electrodes for electrochemical measurements were prepared by blending 90 wt% NMC with 5 wt% polyvinylidene fluoride binder (PVDF 5130, manufacturer: Solef) and 5 wt% conductive carbon black (SUPER PLi, manufacturer: TIMCAL) under an inert gas atmosphere. N-methyl-2-pyrrolidone (NMP) was used as the solvent. The slurry was cast onto an aluminum foil and dried at 120°C for 20 minutes on a heating plate in air. The electrode sheet was then dried in a vacuum oven at 120°C for 2 hours. Circular electrodes with a diameter of 12 mm were punched out from the larger pieces, then flattened between two rollers at a pressure of 90 psi and dried again in a vacuum oven at 120°C for 12 hours to remove any residual water and NMP.

[0085] Lithium Battery Assembly Lithium battery cells for cycle testing were assembled as CR2032 type coin cells (MTI Corporation) in an argon-filled glove box (GLOVEBOX SYSTEMTECHNIK GmbH). Lithium metal (ROCKWOOD LITHIUM GmbH) was used as the anode material. Celgard 2500 was used as the separator. LiPF in ethylene carbonate and ethyl methyl carbonate 6 (50:50 weight / weight; SIGMA-ALDRICH) was used as the electrolyte. The cell was clamped with a crimper (MTI).

[0086] Constant Current Cycle Test The galvanostatic cycling performance of the assembled lithium cells was measured at 25 °C using a MACCOR battery cycler with cutoff voltages of 3.0 to 4.3 V. The C-rate (charge / discharge) was increased every 4 cycles starting from 0.1 C / 0.1 C (charge / discharge) to 0.3 C / 0.3 C, 0.5 C / 0.5 C, 1.0 C / 1.0 C, 1.0 C / 2.0 C, and 1.0 C / 4.0 C. The cells were then cycled at 0.5 C / 0.5 C for long-term stability testing (the 0.5 C rate was 0.7 mAh / cm). 2 (corresponding to a current density of 1000 mAh / g). Only the mass of active material was considered in the calculation of capacity and specific current. These results are shown in Figure 5. The axes in Figure 5 indicate: x-axis = cycle number; y-axis = discharge capacity (mAh / g).

[0087] In Figure 5, fumed ZrO 2 The cycling performance of the NMC coated with nano-ZrO (triangle line) is 2 The results are compared to a NMC coated with fumed ZrO (circle lines) and an uncoated NMC (square lines) as a reference. 2 It is clear that the coating significantly improves the stability and cycle life of the NMC. 2The NMC coated with "Nano ZrO" shows the highest discharge capacity over all cycles in both the first rate test and the long-term cycle test compared to the other tested materials. It is also noteworthy that this NMC shows a higher initial specific discharge capacity than the other samples at 0.1 °C. 2 The cells with NMC coated with " show significantly worse cycling performance. For this material, the rate performance at a discharge rate of 4C and the capacity retention in long-term cycling tests are even worse than the results for the uncoated NMC.

Claims

1. 1. A method for producing a coated mixed lithium transition metal oxide comprising: subjecting the mixed lithium transition metal oxide and the pyrogenously produced zirconium dioxide and / or the pyrogenously produced mixed oxide comprising zirconium to dry mixing using an electric mixing unit having a specific power of 0.05-1.5 kW / kg of the mixed lithium transition metal oxide; A method according to claim 1, characterized in that the zirconium dioxide and / or the mixed oxide comprising zirconium used to produce the coated mixed lithium transition metal oxide has a BET surface area of ​​5 to 200 m 2 / g.

2. 2. The method according to claim 1, characterized in that the specific power of the mixing unit is 0.1 to 1000 kW.

3. The capacity of the mixing unit used is 0.1 L to 2.5 m 3 The method according to claim 1 or 2, characterized in that

4. Method according to any one of claims 1 to 3, characterized in that the speed of the mixing tool in the mixing unit is between 5 and 30 m / s.

5. 5. The method according to claim 1, wherein the zirconium dioxide and the mixed oxide comprising zirconium used for producing the coated mixed lithium transition metal oxide are in the form of aggregated primary particles, the numerical mean diameter of the primary particles being between 5 and 100 nm, as determined by transmission electron microscopy (TEM).

6. The average particle size d of the zirconium dioxide and / or the zirconium-containing mixed oxide particles used to produce the coated mixed lithium transition metal oxide 50 6. The method according to claim 1 , wherein the particle size distribution is between 10 and 150 nm as determined by static light scattering (SLS) after 60 seconds of ultrasonic treatment at 25° C. of a mixture of 5% by weight of the particles and 95% by weight of a 0.5 g / L aqueous solution of sodium pyrophosphate.

7. The span (d) of the zirconium dioxide particles and / or the zirconium-containing mixed oxide particles used to produce the coated mixed lithium transition metal oxide. 90 -d 10 ) / d 50 7. The method according to claim 1, wherein the particle size distribution is 0.4 to 1.2 as determined by static light scattering (SLS) after 60 seconds of ultrasonic treatment at 25° C. of a mixture of 5% by weight of the particles and 95% by weight of a 0.5 g / L aqueous solution of sodium pyrophosphate.

8. 8. The method according to claim 1, wherein the mixed oxide comprising zirconium further comprises lithium and, optionally, at least one of lanthanum and / or aluminium.

9. 9. The method of any one of claims 1 to 8, characterized in that the mixed lithium transition metal oxide is selected from the group consisting of lithium-cobalt oxide, lithium-manganese oxide, lithium-nickel-cobalt oxide, lithium-nickel-manganese-cobalt oxide, lithium-nickel-cobalt-aluminum oxide, lithium-nickel-manganese oxide, or mixtures thereof.

10. 10. The process according to claim 1, characterized in that the proportion of the zirconium dioxide and / or the mixed oxide containing zirconium is 0.05% to 5% by weight, based on the total weight of the used mixture of the mixed lithium transition metal oxide and the zirconium dioxide and / or the mixed oxide containing zirconium.

11. Number average particle size d of 10 nm to 150 nm 50 1. A coated mixed lithium transition metal oxide comprising pyrogenously produced zirconium dioxide and / or a pyrogenously produced mixed oxide comprising zirconium on a surface of the mixed lithium transition metal oxide having a formula: A coated mixed lithium transition metal oxide, characterized in that the zirconium dioxide and / or the mixed oxide containing zirconium has a BET surface area of ​​5 to 200 m 2 / g.

12. 12. An active cathode material for a lithium battery comprising the coated mixed lithium transition metal oxide of claim 11.

13. A lithium battery comprising the coated mixed lithium transition metal oxide of claim 11.

14. 12. Use of the coated mixed lithium transition metal oxide of claim 11 in the active cathode material of a lithium battery.

Citation Information

Patent Citations

  • Positive-electrode active material for batteries and method for manufacturing the same

    JP2013235666A